The future of coastal management programme in Malaysia: making the coast visible to planners - Asmawi, M. Zainora (Malaysian Institute of Planners, 2012)
The concept of coastal management which is regarded as an effective management tool has been widely used globally for more than 40 years. It works across sectoral, disciplinary and institutional boundaries to manage coastal resources. In many coastal nations, it is highly regarded as an essential approach in formulating coastal strategies and objectives towards a sustainable coastal development. However, the coastal management strategies are currently not extensively incorporated in the institutional framework of Malaysian land use planning system. This situation leads to this study in which it looks into the scenario of the planning practice and coastal management from the perspective of public town planners. For data collection, questionnaire survey was conducted throughout coastal Local Planning Authorities in Peninsular Malaysia. The results revealed that relatively the acceptance of Malaysian planners was rather unsatisfactory. It is clearly evident that lacking of awareness led to disintegrated approach between town planning and coastal management.